Strategi Korporasi PT Martina Berto Tbk dalam Menghadapi Persaingan Industri Kosmetik dan Herbal di Indonesia - Herry Kusumadjaja (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the strategic management of PT Martina Berto Tbk in responding to the increasing competition in the cosmetics and herbal industry in Indonesia. The research employs a qualitative descriptive approach with a case study method, utilizing secondary data from company annual reports and relevant literature. The analysis is conducted using various strategic management tools, including PEST, Five Forces, SWOT, BCG, IE, SPACE, and QSPM matrices. The findings indicate that the company’s strengths lie in its diversified product portfolio, extensive distribution network, and strong brand image based on natural ingredients. However, the company also faces challenges such as intense competition, dependence on imported raw materials, and operational cost pressures. Based on the QSPM analysis, the most appropriate strategy is market penetration, focusing on strengthening digital marketing, expanding distribution channels, and enhancing customer engagement. This strategy is expected to improve competitiveness and support sustainable growth amid industry dynamics.